Rapid synthesis of ultralong Fe(OH)3:Cu(OH)2 core–shell nanowires self-supported on copper foam as a highly efficient 3D electrode for water oxidation. Issue 100 (1st December 2016) - Hou, Chun-Chao; Wang, Chuan-Jun; Chen, Qian-Qian; Lv, Xiao-Jun; Fu, Wen-Fu; Chen, Yong
Abstract : Ultralong Fe(OH)3 :Cu(OH)2 core–shell nanowires were facilely grown on an open 3D Cu electrode to function as a highly efficient electrocatalyst for water oxidation. Abstract : One-dimensional core–shell nanowire materials have recently received great attention as durable catalysts for water splitting. Herein we report the facile and rapid synthesis of ultralong Fe(OH)3 :Cu(OH)2 core–shell nanowires grown in situ on an open 3D electrode to function as a highly efficient electrocatalyst for water oxidation. It only requires an overpotential of ∼365 mV to reach a 10 mA cm −2 current density in 1.0 M KOH. As far as we know, this shows the best result amongst Cu-based heterogeneous OER systems reported to date.